Synthesis of copper sulphide nanoparticles for solar cells applications - Tan, Pei Keng. (2010)
There has been an increase in interest lately to explore the possibility of using hybrid system in solar cells. The reason for this is because of its low cost potential and scalability. This report will discuss on the synthesis of monodisperse copper sulphide (Cu2S) nanoparticles for the application in hybrid solar cells.